Optimization of Occupational Safety and Health Management at PT Aplikanusa Lintasarta Makassar - Amsyir, Nur Shafira Ramadhani; Niswaty, Risma; Isgunandar, Isgunandar (International Journal of Administration and Education, 2025)
Implementing safety and health management in the work environment is always necessary and should be a priority in every company. Occupational safety and health management ensures the well-being and protection of every worker in the workplace. In supporting productivity and achieving common goals, optimal K3 management optimization is needed. This study aims to examine the optimization of occupational safety and health management in the work environment of PT Aplikanusa Lintasarta Makassar. This research is qualitative. Data collection methods such as observation, interviews, and documentation are used to achieve the research objectives. The research participants consisted of five employees of PT Aplikanusa Lintasarta Makassar. The study results show that the management of occupational safety and health in the work environment of PT Aplikanusa Lintasarta Makassar is optimal, as evidenced by "optimal" occupational safety indicators. It can be seen from the completeness of work tools, work safety, employee compliance with the rules, safety, welfare standards, and company rules. Occupational health has been well implemented by the company and directly impacts employee performance; employees become more productive with health and employment insurance. An office environment improves occupational health by providing employees with a comfortable and healthy workspace. The company designs the room according to employees' work needs by creating an open office space for the comfort of employees while working. Office ergonomics is also good, as seen from the availability of room facilities that meet employees' productivity needs. As well as the arrangement of minimalist office furniture following open workspaces.